1980
DOI: 10.1179/030716980803286676
|View full text |Cite
|
Sign up to set email alerts
|

Gradual changes in residual stress and microstructure during contact fatigue in ball bearings

Abstract: Deep-groove ball bearings have been endurance tested at high stress levels. The purpose of the work was to study the simultaneous generation of residual stresses and occurrence of structural changes owing to cyclic rolling contact fatigue. During the investigation the decomposition of both retained austenite and parent martensite were followed. The residual stresses and the austenite decomposition were measured by an X-ray diffraction technique, using signal averaging. Optical and transmission electron microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
80
2

Year Published

1982
1982
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(93 citation statements)
references
References 7 publications
4
80
2
Order By: Relevance
“…The gradient in plastic response of these case hardened bearing steels can be used to design bearing raceways that have longer RCF lives while at the same time withstand higher thrust loads. Subsurface white etching bands (WEB) and dark etching regions (DER) have been found in life endurance tested bearings and are believed to undermine the integrity and fatigue life of rolling element bearings (Voskamp et al, 1980;Forster et al, 2010). Knowledge of the gradient in flow curve in this region will help model the elastic-plastic stress field in the RCF-affected case layer which will aid in understanding such phenomenon.…”
Section: Reverse Analysis For Plastically-graded Case Hardened M50 Nilmentioning
confidence: 98%
“…The gradient in plastic response of these case hardened bearing steels can be used to design bearing raceways that have longer RCF lives while at the same time withstand higher thrust loads. Subsurface white etching bands (WEB) and dark etching regions (DER) have been found in life endurance tested bearings and are believed to undermine the integrity and fatigue life of rolling element bearings (Voskamp et al, 1980;Forster et al, 2010). Knowledge of the gradient in flow curve in this region will help model the elastic-plastic stress field in the RCF-affected case layer which will aid in understanding such phenomenon.…”
Section: Reverse Analysis For Plastically-graded Case Hardened M50 Nilmentioning
confidence: 98%
“…Weiss et al [11,12] have shown that in 304L and 316 stainless steels cycled in axial tensiontension loading above the monotonic yield strength, rapid relaxation of the initial compressive residual stress takes place and subsequent development of a tensile stress occurs. Voskamp et al [13] have reported that during overrolling in the inner ring of a deep-groove ball bearing, the initially tensile residual stresses just below the surface progressively decrease with fatigue and then change to compressive stresses which continue to increase in magnitude with further deformation. McClinton and Cohen [14] have shown that tensile residual stresses develop within the plastic deformation bands of an annealed mild steel, even at loads close to the fatigue limit in tension-tension fatigue.…”
Section: Fatigue Above the Yield Strengthmentioning
confidence: 98%
“…The versatility of various XRD systems makes them suitable for utilization in such characterization routines as quantitative phase identification, crystal structure determination, and residual stresses measurements, to name a few [1]. Extensive studies [2][3][4][5] have incorporated into their recorded results measurements of residual stresses, proportions of retained austenite and martensite, or a combination of these measurements to correlate the effect of phase transformations to the resultant magnitude of residual stresses. Like other nondestructive testing techniques, however, XRD has limitations.…”
Section: Introductionmentioning
confidence: 99%